Influence of Raman Spectroscopy Test Conditions on the Results of Carbon Chemical Structure of Chars - Jiangyong He; Chong Zou; Junxue Zhao; Jiale Xi; Yuan She; Mengmeng Ren; Yufen Xu (Energies, 2022)
To address the problem of variability in in situ Raman spectroscopy for determining the chemical structure of chars, the rationality of Raman’s original peak spectrum fitting method, the influence of objective lens magnification, particle size, and number of measurements on peak shape and characteristic parameters were investigated. The results show that the Raman original peak spectrum of char is fitted by five peaks and the goodness of fit is best when the D3 peak is fitted by a Gaussian curve. The intensity of the peak spectrum and stability of the characteristic parameters of the Raman spectroscopy are related to the objective lens magnification. For a relatively large objective lens magnification, the Raman peak spectrum intensity is increased and the coefficient of variation in the characteristic parameters is accordingly reduced. As particle size increases, the characteristic parameters AG/AAll that characterize the perfect graphite structure decrease and the characteristic parameters AD1/AAll, AD3/AAll, and AD1/AG that characterize the defective graphite structure increase. The coefficient of variation for the characteristic parameters is found to be the smallest for the particle size range of 81–96 μm. Micro-Raman imaging reveals that the microscopic characteristic parameters of different micro zones are significantly different and the number of measurements required to achieve reliable Raman characteristic parameters is related to this anisotropy.